Meningkatkan Hasil Belajar Materi Cerita Pendek melalui Model Pembelajaran RADEC dengan Media Mini Teater pada Kelas 3 SDN Pojok 1 Kediri - Muchlishoh, Lailatul; Jatmiko; Lestari, Dwi Puji (PTK: Jurnal Tindakan Kelas, 2025)
The role of teachers as the sole source of learning in learning has an impact on the low level of active student involvement, then their learning outcomes become low. Innovative learning is needed to overcome existing problems. The selection of the RADEC model and mini theater media is because each stage in the RADEC model can develop student activeness in learning Indonesian while the media is chosen to support learning as a means for students to easily understand concepts and develop their literacy skills. This study aims to improve the learning outcomes of grade 3 students of SDN Pojok 1 Kediri in the Indonesian language subject, especially short story material, through the application of the RADEC learning model combined with mini theater media. This classroom action research adopts the Kemmis and Mc. Taggart model, which consists of a cycle of planning, implementing actions, observation, and reflection as a series of continuous processes. Student learning outcomes always increase, namely in cycle 1 it was 61%, followed by a significant increase in cycle 2 of 96%. The findings of the study indicate that through the RADEC learning model and the presentation of mini theater media, student learning outcomes increased.